2016
DOI: 10.1111/pce.12756
|View full text |Cite
|
Sign up to set email alerts
|

HD2C histone deacetylase and a SWI/SNF chromatin remodelling complex interact and both are involved in mediating the heat stress response in Arabidopsis

Abstract: Studies in yeast and animals have revealed that histone deacetylases (HDACs) often act as components of multiprotein complexes, including chromatin remodelling complexes (CRCs). However, interactions between HDACs and CRCs in plants have yet to be demonstrated. Here, we present evidence for the interaction between Arabidopsis HD2C deacetylase and a BRM-containing SWI/SNF CRC. Moreover, we reveal a novel function of HD2C as a regulator of the heat stress response. HD2C transcript levels were strongly induced in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 62 publications
3
78
0
Order By: Relevance
“…Our detailed genetic, molecular and biochemical data showed that LFR was involved in the regulation of petioles length and midvein formation, and leaflet‐like structure elongation by repressing BP expression together with AS2 (Figure ). Previous reports indicated that Arabidopsis LFR may co‐exist with the SWI/SNF complex in Arabidopsis (Wang et al ., ; Vercruyssen et al ., ; Buszewicz et al ., ; Sarnowska et al ., ), and we also detected the interaction between AS1–AS2 and some putative SWI/SNF complex subunits (Figure ). Coincidentally, AS1 was screened as a potential interacting partner of BRAHMA (BRM, an ATPase of SWI/SNF complex) in Y2H screening (Efroni et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…Our detailed genetic, molecular and biochemical data showed that LFR was involved in the regulation of petioles length and midvein formation, and leaflet‐like structure elongation by repressing BP expression together with AS2 (Figure ). Previous reports indicated that Arabidopsis LFR may co‐exist with the SWI/SNF complex in Arabidopsis (Wang et al ., ; Vercruyssen et al ., ; Buszewicz et al ., ; Sarnowska et al ., ), and we also detected the interaction between AS1–AS2 and some putative SWI/SNF complex subunits (Figure ). Coincidentally, AS1 was screened as a potential interacting partner of BRAHMA (BRM, an ATPase of SWI/SNF complex) in Y2H screening (Efroni et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…Some of the changes that we observed may not be due to the specific catalytic functions of BRM or inherent properties of H2A.Z incorporation into chromatin by the SWR1 complex but rather be contributed by other chromatin regulating factors that interact with them. The SWI2/SNF2 complex is known to interact with a histone acetyl transferase (HD2C), a H3K27me3 histone demethylase (REF6), and potentially the ISWI CRC (Brzezinka et al, 2016;Buszewicz et al, 2016;Li et al, 2016). BRM also antagonizes the function of the Polycomb Repressive Complex 2, so some of the nucleosomal changes we observe may not be due to a direct contribution by BRM but a result of nucleosomal changes that come with Polycomb repressive complex associated silencing activity (Li et al, 2015a).…”
Section: Other Chromatin Factors May Contribute To the Roles Of Brm Amentioning
confidence: 93%
“…For example, both H2A.Z and the SWI2/SNF2 complex have been implicated in regulating chromatin accessibility for TFs (John et al, 2008;Sacharowski et al, 2015;Jegu et al, 2017). H2A.Z eviction from +1 nucleosomes is regulated by the HSFA1a TFs to regulate heat response genes (Cortijo et al, 2017) and conversely BRM can be recruited to chromatin by TFs (Wu 2012;Efroni et al, 2013;Vercruyssen et al, 2014;Zhao et al, 2015;Buszewicz et al, 2016;Zhang et al, 2016). These previously defined relationships between H2A.Z, BRM, and TFs prompted us to evaluate how H2A.Z and BRM contribute to nucleosome organization surrounding TF binding sites where they colocalize.…”
Section: Brm and H2az May Interact With Tfs To Facilitate Transcriptmentioning
confidence: 99%
“…However, H2A.Z and/or BRM may have more consistent roles in chromatin regulation through interactions with specific transcription factors (TFs). Some previously reported interactions between either H2A.Z or BRM and TFs prompted us to evaluate how H2A.Z and BRM might contribute to nucleosome organization surrounding TF binding sites where they co-localize (John et al, 2008;Wu, 2012;Efroni et al, 2013;Vercruyssen et al, 2014;Sacharowski et al, 2015;Zhao and Garcia, 2015;Buszewicz et al, 2016;Cortijo et al, 2017;Jegu et al, 2017;Zhang et al, 2017a).…”
Section: Brm and H2az May Interact With Tfs To Facilitate Transcriptmentioning
confidence: 99%
“…Additional factors may contribute to the roles of BRM and H2A.Z in chromatin organization and transcriptional regulation Some of the transcriptional and nucleosomal changes that we observed in brm or arp6 mutants may not be due to the specific catalytic functions of BRM or inherent properties of H2A.Z incorporation into chromatin by the SWR1 complex, but could rather be contributed by other chromatin-regulating factors that interact with them. The SWI2/SNF2 complex is known to interact with a histone acetyltransferase (HD2C), a H3K27me3 histone demethylase (REF6), and potentially the ISWI CRC (Brzezinka et al, 2016;Buszewicz et al, 2016;Li et al, 2016). BRM also antagonizes the silencing function of the Polycomb Repressive Complex 2 (Li et al, 2015).…”
Section: Brm and H2az Interact With Binding Sites For Lightresponsivmentioning
confidence: 99%